Pemberdayaan Masyarakat Melalui Pengolahan Abon Ampas Tahu Ramah Lingkungan - Adistira, Ross Mellyana; Lestari, Vivi Ayu; Putri, Cindyana Sabila; Sari, Maya Intan; Zahra, Dhifa Nadia; Indewi, Fitri; Maharani, Aida; Putri, Nagita Ananda; Purnama, Rizki (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Tofu dregs waste in Dusun 6 Wonodadi has not been optimally utilized and has the potential to cause environmental pollution due to improper disposal. In fact, tofu dregs still contain relatively high nutritional value and can be processed into economically valuable food products. This community service program aims to empower the community through training in processing tofu dregs waste into shredded products (abon) as a solution to increase income while maintaining environmental cleanliness. The methods used include socialization, counselling, hands-on training, and assistance in packaging and simple marketing. The results show an improvement in community knowledge and skills in processing tofu dregs into edible shredded products with market value. In addition, there was an increase in community awareness regarding the importance of environmentally friendly waste management. This program demonstrates that processing tofu dregs into shredded products can be an effective strategy for economic empowerment and sustainable environmental pollution reduction.